Association between beta‐blocker atenolol use and prostate cancer upgrading in active surveillance1 - Ali H. Zahalka; Ethan Fram; Evan Garden; Lauren Howard; Emily Wiggins; Mustufa Babar; Jay Annam; Allison Reagan; Benjamin Eilender; Amanda deHoedt; Stephen J. Freedland; Ash Tewari; et al. (BJUI Compass)
Abstract Objectives The objective of this study is to investigate the association between the use of beta‐adrenergic antagonist atenolol and risk of pathologic upgrade in patients on active surveillance, considering growing literature implicating adrenergic innervation with disease progression mediated through beta‐adrenergic signalling. Patients and Methods Men with low‐risk or favourable intermediate‐risk prostate cancer who were placed on an active surveillance protocol between 2006 and 2020 across three diverse urban hospitals were included. Exposure was duration of atenolol use, and outcome was pathologic grade group upgrading (to GG ≥ 3) on final prostate biopsy. Cox proportional hazard regression models were used to determine the associations between atenolol use and risk of upgrading with time, on a per‐examination basis. Results A total of 467 men with initial GG ≤ 2 were included. Postdiagnosis atenolol use was associated with a decreased risk of pathologic upgrade to GG ≥ 3 on final repeat biopsy (HR 0.81, 95% CI 0.39–0.98). Longer duration of postdiagnosis atenolol use (>2 years) and greater cumulative atenolol dose (>730 defined daily doses) were associated with a more pronounced decreased risk of upgrade to GG ≥ 3 (HR 0.41, 95% CI 0.05–0.88, and HR 0.32, 95% CI 0.15–0.99, respectively). Initiation of atenolol use prior to prostate cancer diagnosis had a slightly greater protective effect than drug initiation postdiagnosis (HR 0.79, 95% CI 0.43–0.98, and HR 0.83, 95% CI 0.30–0.99, respectively). Conclusions Beta‐adrenergic blockade with atenolol use in men on active surveillance is associated with a reduced risk for clinically significant grade group pathologic upgrade.